THE EFFECT OF THE NUMBER OF TOURIST OBJECTS, NUMBER OF TOURISTS, NUMBER OF HOTELS AND NUMBER OF RESTAURANTS ON REGIONAL OWN SOURCE REVENUE (ROSR) OF EAST JAVA PROVINCE - Faros Hafidz Muhammad Trizhardi; Arief Bachtiar (Publikasi Inspirasi Indonesia, 2026)
This study aims to analyze the influence of the tourism sector on Regional Own-Source Revenue (ROSR) in East Java Province during the 2017–2024 period by examining four key variables: the number of tourist attractions, tourist visits, hotels, and restaurants. The research is motivated by the discrepancy between East Java’s substantial tourism potential—consistently recording the highest domestic tourist visits in Indonesia—and its relatively small contribution to ROSR compared to other revenue sources such as motor vehicle taxes. Using panel data from six regencies/cities and multiple linear regression analysis, this study provides an empirical overview of how tourism indicators affect the fiscal capacity of the region. The findings show that tourist attractions, hotels, and restaurants have a positive and significant effect on ROSR, while the number of tourists does not exhibit a significant influence. This indicates that tourist activities are not fully captured within the regional tax system and remain largely within informal sectors. Simultaneously, all tourism variables significantly affect ROSR, supporting the Tourism-Led Growth theory and the concept of the multiplier effect. The study concludes that improving the quality and management of tourist attractions, accommodation, and the culinary sector plays a more critical role in enhancing fiscal revenue than merely increasing tourist numbers. These results provide strategic insights for local governments in strengthening the tourism sector's contribution to ROSR.